Surgical Management of Anterolateral and Posteromedial Incisural Tentorial Meningioma. Issue 2 (7th November 2017) - Talacchi, Andrea; Biroli, Antonio; Medaglia, Stefano; Locatelli, Francesca; Meglio, Mario
Abstract: BACKGROUND: Tentorial meningiomas are a broad and consistent category of tumors but their definition is still unclear and their classification uncertain. OBJECTIVE: To report the clinical and surgical characteristics of tentorial hiatus meningiomas based on a revised classification of tentorial meningiomas. METHODS: We reviewed the records of 14 patients who had undergone microsurgical removal of incisural tentorial meningioma. Two tumor subgroups, anterolateral (AL) and posteromedial (PM), were distinguished according to their site of attachment: the middle third and the posterior third of the tentorial free margin, respectively. Clinical presentation, radiological findings, surgical approaches, extent of resection, and outcome were compared. RESULTS: The 2 subgroups differed by tumor size (larger in PM), incidence of the direction of growth (infratentorial in PM), and hydrocephalus (only in PM), as well as by some clinical aspects. Surgical approach depended on tumor location: lateral (pterional, subtemporal, and retromastoid) for AL lesions; medial (occipital or supracerebellar infratentorial) for PM lesions. Total removal (Simpson grade I-II) was performed in 64% of cases and complications occurred in 14%. Stereotactic radiosurgery was performed in cases of incomplete resection. At a mean follow-up of 104.5 mo, clinical improvement with low recurrence (9%) was achieved. CONCLUSION: Reallocation of tentorial edge meningiomas is the premise to compare treatment and further improve the approach case-by-case. In spite of their deep site, good outcomes can be achieved in both AL and PM tentorial meningiomas. Also of note is the indolent behavior of residual tumor.